Cooperative Networking in a Heterogeneous Wireless Medium - Ismail, Muhammad; Zhuang, Weihua; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2013)
This brief focuses on radio resource allocation in a heterogeneous wireless medium. It presents radio resource allocation algorithms with decentralized implementation, which support both single-network and multi-homing services. The brief provides a set of cooperative networking algorithms, which rely on the concepts of short-term call traffic load prediction, network cooperation, convex optimization, and decomposition theory. In the proposed solutions, mobile terminals play an active role in the resource allocation operation, instead of their traditional role as passive service recipients in the networking environment.
Introduction -- Decentralized Optimal Resource Allocation -- Prediction Based Resource Allocation -- Resource Allocation for Single-network and Multi-homing Services -- Conclusions and Future Directions.
Keywords: Engineering; Computer system performance; Coding theory; Telecommunication; Engineering; Communications Engineering, Networks; System Performance and Evaluation; Coding and Information Theory